Use of the smart cities concept to rethink the Municipal Council communication processes - Quilice, Thiago Ferreira; Silva, Cleiton Martins Duarte da; Jácome, Naraiana Marques; Sanches, Poliana Estefane (Revista de Administração da UFSM, 2020)
The concept of smart cities addresses how information technology can improve a city’s processes and suggests greater participation among the population in these processes. The purpose of this article was to use this concept as a support to rethink the communication processes of municipal councils, seeking ways to improve them through the use of information technologies, which would allow improving the structure for the dissemination of actions taken by the councils and increasing social control over public policy planning and implementation. For this, the communication processes of the municipal councils of a small city were analyzed. These processes were then evaluated and discussed in light of the concept of smart cities. As a result, it was found that the communication processes analyzed are flawed and need improvement, especially regarding their scope, which should include the possibility of manifestation by society. Initiatives related to the concept of smart cities that could solve the identified problems are also discussed. Based on the collected data, the requirements and functionalities for the development of a technology-based communication tool that could enable faster and more effective communication between the counselors, between the councils and society and between the councils and their government departments are suggested. Finally, it is suggested that future research assesses within the population the reasons why social participation in municipal councils is low.